PERBEDAAN STRES KERJA BERDASARKAN SHIFT KERJA PADA PEKERJA BAGIAN ELECTRICAL FIELD SERVICE DI PT. BAKER HUGHES INDONESIA DURI-RIAU TAHUN 2013 - Mayan Sari Hasibuan; Kalsum .; Halinda Sari Lubis (Lingkungan dan Kesehatan Kerja, 2013)
The differences in work stress based on working shifts at Electrical Field Service workers in PT. Baker Hughes Indonesia Duri – Riau 2013. Job stress disorder is the negative reaction that arising caused by work performed. A variety of factors can contribute to a person feeling stressed at work including the work shift, where workers will experience a different work situations between the day shift and night shift. This research is aimed to look the differences work related stress that occurred due to the work shift on electrical field service workers at PT. Baker Hughes Indonesia Duri-Riau, 2013. This research is an analytical survey using cros sectional design. The population in this research was 27 electrical field service workers and the sample was the total population. The measurement of job stress using a questionnaire and analyzed using the Wilcoxon test with significance level (α) of 5%. Wilcoxon test results obtained using a significance value of 0.02 (p <0.05), in order to obtain the result that there is a significant difference in job stress based on working shift, and the most experienced high job stress is when the night shift as many as 13 workers (48.15%). Suggested to the company to pay attention and listen to the grievances of the workers, especially in night shift workers, and for workers are advised to always used the waiting time for positive activities. Ker Words: Work Stress, Shift Work, Electrical Field Service